1977
DOI: 10.1073/pnas.74.5.2069
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced flow through living sponges in nature.

Abstract: Flow velocities through and immediately adjacent to the excurrent openings (oscula) were measured in eight species of marine sponges in their natural environments with a two-channel thermistor flowmeter. Flow through the oscula was positively correlated with both normal and artificially augmented ambient flow in both normally pumping and inactive animals. These results indicate that the passage of water through these sponges is, in part, induced by ambient currents.As a consequence of any of several physical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
2
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(166 citation statements)
references
References 3 publications
(3 reference statements)
5
154
2
5
Order By: Relevance
“…They possessed the tallest protuberances with the largest terminal oscula. Their shape is correlated with the generally low flows found within their protected minicave habitat and is supported by the concept that oscula placed high on protuberances help insure maximum separation of ejected metabolic wastes and new oxygenated water and food particles entering the ostia at the surface of the sponge (Vogel 1977(Vogel , 1994.…”
Section: Sponge Body Forms and Water Flow Regimesmentioning
confidence: 81%
See 2 more Smart Citations
“…They possessed the tallest protuberances with the largest terminal oscula. Their shape is correlated with the generally low flows found within their protected minicave habitat and is supported by the concept that oscula placed high on protuberances help insure maximum separation of ejected metabolic wastes and new oxygenated water and food particles entering the ostia at the surface of the sponge (Vogel 1977(Vogel , 1994.…”
Section: Sponge Body Forms and Water Flow Regimesmentioning
confidence: 81%
“…From published studies on sponge fluid mechanics (RiisgĂ„rd et al 1993;Vogel 1977Vogel , 1994, we know that Fig. 7 Sponge at site B, with the thermistor probe placed above an osculum.…”
Section: Flow Visualization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…through viscous entrainment from the posterior nostril. Vogel (1977b) has reported that flow through living sponges, driven by flagella within their interiors, may be assisted by an external current, so there is a precedent for a combined mechanism of this sort in Nature. In at least one case, the lemon shark (Negaprion brevirostris), two mechanisms-the beating of cilia and (probably) an external flow-must act cooperatively to ventilate the organ, each mechanism on its own being insufficient (Zeiske et al 1987(Zeiske et al , p. 2411.…”
Section: Discussionmentioning
confidence: 99%
“…Some marine species filter 24 000 1 kg-' body weight d-' (Vogel 1977) or pump a volume of water equal to their own body volume every 5 s (Reiswig 1974). Hence they 'Corresponding author.…”
Section: Introductionmentioning
confidence: 99%